FENOMENA JANUARY EFFECT DI BURSA EFEK INDONESIA PADA PERUSAHAAN MANUFAKTUR SUBSEKTOR FOOD AND BEVERAGE - Theresia Dhian Kusumawati (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2017)
Investment in stocks is currently a matter that is in demand by various groups, therefore therelevant information is needed by the investor, the analysis january effect on the manufacturing subsector of food and beverage into one benchmark to see how the condition of the company. This studyaims to determine whether the january effect occurs in food and beverage manufacturing companies,this type of research is descriptive quantitative research and data sources used are secondary dataannouncement stock prices in 2014-2015 were obtained from IDX sites, namely: (www.idx .co.id) that isthe object of the research data were processed using a comparative analysis of stock returns. Tax LossSelling most popularly associated with the January Effect is a Tax-Loss Selling hypothesis in whichinvestors sell shares to fall in value. window DressingWindow dressing is the selloff in stocks that memilikikinerja bad end of the year. Windowdressing is not much different from the Tax Loss Selling, where it inidilakukan by financial managerswith the aim that the performance report stock portfolio at year-end will look good performance. Fromthese results it can be concluded that not all companies affected by the January effect, this occurs dueto many factors, including large companies, and how long a company listed on the Stock Exchange.